2021
DOI: 10.1158/1940-6207.capr-20-0607
|View full text |Cite
|
Sign up to set email alerts
|

Local Anti–PD-1 Delivery Prevents Progression of Premalignant Lesions in a 4NQO-Oral Carcinogenesis Mouse Model

Abstract: While the principle of systemic treatment to prevent the progression of oral premalignant lesions (OPLs) has been demonstrated, there remains a lack of consensus about an optimal approach which balances clinical efficacy with toxicity concerns. Recent advances in cancer therapy using approaches targeting the tumor immune microenvironment (TIME) including immune checkpoint inhibitors indicate that these agents have significant clinically activity against different types of cancer including oral cancer and there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
(54 reference statements)
1
15
0
Order By: Relevance
“…Furthermore, we detected that the protein levels of STING were significantly lower in OPLs expressing mutant Trp53-R172H compared with wild-type Trp53. In addition, we observed a significant reduction of infiltrated DC cells in OPLs expressing mutant p53 (88). While infiltrating immune cells retain wild-type p53 and have normal STING, mutant p53 OPLs have decreased immune cell infiltration and may not compensate for reduced STING expression in lesions with mutant TP53.…”
Section: Tp53mentioning
confidence: 74%
See 4 more Smart Citations
“…Furthermore, we detected that the protein levels of STING were significantly lower in OPLs expressing mutant Trp53-R172H compared with wild-type Trp53. In addition, we observed a significant reduction of infiltrated DC cells in OPLs expressing mutant p53 (88). While infiltrating immune cells retain wild-type p53 and have normal STING, mutant p53 OPLs have decreased immune cell infiltration and may not compensate for reduced STING expression in lesions with mutant TP53.…”
Section: Tp53mentioning
confidence: 74%
“…This study not only showed the capacity of the hydrogels to control the release of PD-1 antibody and reduce OPL frequency, but also provided evidence of the role of mutant p53 in the mechanism of immunosuppression in OPLs. Other immunoprevention studies using p53 mutant mice have showed similar results but required 8 doses of parental immunotherapy administration (89,123), compared to a single hydrogel-PD1 dose (88). A recent comprehensive study of patient samples of leukoplakia identified that proliferative leukoplakia predicts a high rate of malignant transformation within 5 years of diagnosis.…”
Section: Reversing Immunosuppression In Oplmentioning
confidence: 90%
See 3 more Smart Citations